Infantile Hemangioma: A Retrospective Study - Eva Lydiawati; Iskandar Zulkarnain (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2020)
Background: Infantile Hemangioma (IH) is a benign vascular neoplasm and most commonly found in newborns. IH appears in the first few weeks of life and mostly resolve immediately. Early recognition of symptoms, diagnosis, and therapy has an important role in determining the prognosis of this condition. Purpose: The purpose of this study is to evaluate the clinical features of new IH patients in the Pediatric Dermatology Division of the Dermatology & Venereology Department outpatient clinic of Dr. Soetomo General Hospital Surabaya in 2008-2017. Methods: This is a retrospective descriptive study from the medical records of new IH patients over a period of 10 years (2008-2017). Results: A total of 84 new IH patients were observed in this study. The data showed that: the most age group was 0-1 year old (71.43%), female (63.1%), and no family history of a similar condition (94.05%). The most common complaint reported was the presence of bumps (59.52%). Most complaints occurred before the patients turned one year old (89.29%) and involved the facial region (58.33%). From the clinical features, the most frequent skin lesions were macules (35.36%). In addition, there was a combination of macular and nodular lesions in 28.13% of patients. The most widely used therapy is laser modality found in 55.45% of patients. Conclusion: Clinical features of IH patients, in accordance with the theory and treatment choices, dependent on the patients’ conditions and clinical manifestations of the disease.